2002
DOI: 10.1161/01.cir.0000038497.80095.e1
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Neurohumoral Effects of Selective Endothelin A (ET A ) Receptor Blockade in Chronic Heart Failure

Abstract: Background— The endothelin (ET-1) system is activated in chronic heart failure (CHF). Whether, what type, and what degree of selective ET blockade is clinically beneficial is unknown. We investigated hemodynamic and neurohumoral effects of 3 weeks of treatment with various dosages of the orally available ET A antagonist darusentan in addition to modern standard therapy in patients with CHF. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
1
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(116 citation statements)
references
References 40 publications
7
98
1
9
Order By: Relevance
“…These findings of ET-1-induced diminished contractile function are parallel with previously reported in vivo effects (26). Also consistent with our findings, several clinical trials [Endothelin Antagonism with Bosentan and Lowering Events (ENABLE), Endothelin A Receptor Antagonist Trial in Heart Failure (EARTH), Randomized Intravenous TeZosentan Study (RITZ-4), and Heart Failure ET A Receptor Blockade Trial (HEAT)] have shown that systolic function and cardiac contractility are maintained by ET-1 receptor blockade, yet unfortunately morbidity and mortality were not improved (25,34,42). These studies evaluated patients with extensive myocardial remodeling (New York Heart Association class II to IV) with the intent of ameliorating progressive deterioration of existing ventricular dysfunction.…”
Section: Effect Of Et Receptor Antagonism On Postfistula Remodeling Asupporting
confidence: 92%
“…These findings of ET-1-induced diminished contractile function are parallel with previously reported in vivo effects (26). Also consistent with our findings, several clinical trials [Endothelin Antagonism with Bosentan and Lowering Events (ENABLE), Endothelin A Receptor Antagonist Trial in Heart Failure (EARTH), Randomized Intravenous TeZosentan Study (RITZ-4), and Heart Failure ET A Receptor Blockade Trial (HEAT)] have shown that systolic function and cardiac contractility are maintained by ET-1 receptor blockade, yet unfortunately morbidity and mortality were not improved (25,34,42). These studies evaluated patients with extensive myocardial remodeling (New York Heart Association class II to IV) with the intent of ameliorating progressive deterioration of existing ventricular dysfunction.…”
Section: Effect Of Et Receptor Antagonism On Postfistula Remodeling Asupporting
confidence: 92%
“…These results explain how ET A i improves local NE homeostasis as also shown in DS rats on a high-salt diet. However, why did selective ET A i not result in reduced plasma NE levels in HF patients (11,31)? This discrepancy might be explained by the idea that plasma NE levels are not ideal surrogates for the local cardiac adrenergic drive but rather serve as a marker for a generalized sympathetic activation.…”
Section: Discussionmentioning
confidence: 99%
“…28) Previous experimental studies have suggested that increased ET-1 and subsequent activation of ET A receptors played a key role in the pathophysiological changes in HF and blockade of the ET system with ERA could effectively ameliorate survival, LV dysfunction, and ventricular remodeling in acute or cardiomyopathy HF models. [29][30][31] Furthermore, several clinical trials confirmed the ability of ERA to improve the hemodynamics of HF [14][15][16] and a recent study 11) found that sitaxsentan was likely to increase exercise tolerance in HFpEF patients. However, the effect of ERA on clinical outcomes of HF patients needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 92%
“…After title and abstract screening, 2,972 were excluded and 40 potentially relevant articles were retrieved for full text evaluation. In the end, 25 were excluded (Supplementary Table I) and 15 2,9,11,[14][15][16][17][18][20][21][22][23][24][25][26] RCTs that met the predetermined criteria were included in the present study. Major characteristics of the included RCTs are summarized in the Table. In general, the 15 studies, covering a total of 3,624 patients, were published between 1998 and 2013.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation